Interfacial shear in adiabatic downward gas/liquid co-current annular flow in pipes - Aliyu, Aliyu M.; Lao, Liyun; Almabrok, Almabrok Abushanaf; Yeung, Hoi (Elsevier, 2015)
Interfacial friction is one of the key variables for predicting annular two-phase flow behaviours in vertical pipes. In order to develop an improved correlation for interfacial friction factor in downward co-current annular flow, the pressure gradient, film thickness and film velocity data were generated from experiments carried out on Cranfield University’s Serpent Rig, an air/water two-phase vertical flow loop of 101.6 mm internal diameter. The air and water superficial velocity ranges used are 1.42–28.87 and 0.1–1.0 m/s respectively. These correspond to Reynolds number values of 8400–187,000 and 11,000–113,000 respectively. The correlation takes into account the effect of pipe diameter by using the interfacial shear data together with dimensionless liquid film thicknesses related to different pipe sizes ranging from 10 to 101.6 mm, including those from published sources by numerous investigators. It is shown that the predictions of this new correlation outperform those from previously reported studies.
Keywords: Annular flow; Interfacial friction factor; Interfacial shear stress; Multiphase flow; Pressure gradient; Vertical downward flow